Building resilience to adverse childhood experiences: An assessment of the effects of the Stepping Stones with Children training programme on Tanzanian children affected by HIV and their caregivers. (March 2019) - Holden, Sue; Gordon-Dseagu, Vanessa LZ; Gordon, Gill; Chiziza, Nelson; Kiwia, Pfiriaeli; Magesa, Daniel; Manyama, Willbrord; Welbourn, Alice
Objective: To evaluate the effects of a transformative training programme on children aged 5–14 years affected by HIV and their caregivers. Method: A formative process was used to draft, pilot and finalise training materials in Tanzania. We ran workshops with children living with HIV, their caregivers and some siblings in four communities. We assessed changes in knowledge, attitudes and well-being, and compared the health of child participants living with HIV with that of a control group of children living with HIV. Results: Although we intentionally excluded 'disclosure' of HIV sero-status to children as an indicator, the proportion who knew their sero-status increased from 27% to 93%. Assessment of clinical data before and after the workshops showed a statistically significant increase ( p -value of <.01) in the CD4 count among the child participants living with HIV ( n = 85, mean CD4 change + 317; from 530 to 847) compared with the control group ( n = 91, mean CD4 change + 133; from 557 to 690). The mean weight gain was 3.51 kg for child participants and 1.33 kg for controls. Other benefits included improved relationships and reduced violence against the children, greater confidence, more willingness to use HIV services and better networks of support. Conclusion: The Stepping Stones with Children programme can achieve multiple outcomes, including disclosure and better adherence to treatment, to reduce the impact of the adverse childhood experience of being affected by HIV. It is possible and acceptable to include children aged five and over in learning about HIV, sexual health and skills to improve their resilience.